Will the Adoption of Science Standards Push Maine Schools Away from Authentic Science? - Zoellick, Bill; Page, Jennifer (Maine Policy Review, 2017)
Maine is considering revision of rules that provide guidance to school districts about the science knowledge students are expected to have as they graduate from high school. Some science educators suggest adoption of the Next Generation Science Standards (NGSS) as a substantial component of the rules. In this paper, we argue that the NGSS are overly prescriptive and narrow and that a NGSS-based standard would push science instruction toward school science where outcomes are known in advance and away from authentic science where students explore questions that are useful to the community because answers are not yet known. Our experience has been that authentic science learning is more likely to re-engage students who have decided that science learning is for others, not for them. We seek to stimulate a deep, careful consideration of the consequences of moving toward standards based on the NGSS.